2003
DOI: 10.1107/s1600536803005166
|View full text |Cite
|
Sign up to set email alerts
|

1H-Nicotinamidium 3,5-dinitrosalicylate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.003 A Ê Disorder in main residue R factor = 0.040 wR factor = 0.110 Data-to-parameter ratio = 9.6For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…Figures 2 and 3 show the ZORTEP plot of the molecules of BCIC and BCCI with thermal ellipsoids at 30% probability level. The bond lengths and bond angles of the imidazole moiety in BCIC and BCCI are comparable with the standard values [12,13]. The C-C1 distances (C4-C112¼) 1.712(2) Å and 1.723(4) Å are within the range of values reported in the literature [14].…”
Section: Resultssupporting
confidence: 83%
“…Figures 2 and 3 show the ZORTEP plot of the molecules of BCIC and BCCI with thermal ellipsoids at 30% probability level. The bond lengths and bond angles of the imidazole moiety in BCIC and BCCI are comparable with the standard values [12,13]. The C-C1 distances (C4-C112¼) 1.712(2) Å and 1.723(4) Å are within the range of values reported in the literature [14].…”
Section: Resultssupporting
confidence: 83%
“…It has been suggested that the active form of ASPIRIN is, in fact, a copper complex formed in vivo [11]. A substantial effort has been devoted to the synthesis and study of solid copper(II)-salicylato complexes in our laboratories as well [12][13][14][15][16][17][18][19], bearing in mind, however, that both the copper(II) ions and the active organic molecules act in the cell, i.e. in 0162-0134/$ -see front matter Ó 2007 Elsevier Inc. All solution.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are inactive ligands that are activated by copper(II) [8]. Synthesis and characterization of solid copper(II)-salicylato complexes have been carried out in our laboratories as well [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%